Design a simple distillation project-based on chemical literacy on the topic of the alcohol phase F - Meylinda Anggraini; Eka Yusmaita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to design a simple distillation project on chemical literacy on alcohol phase f. This research was designed using the Plomp development model, which consists of 3 stages: the preliminary research stage, the development stage or prototyping, and the assessment stage. In this study, the authors limit the research to the development stage prototype, which produces prototype III. This project was designed using the project-based learning model with a combination of the anatomy of the project-based learning model) and project-based learning syntax, which contains aspects of chemical literacy. The development of this simple distillation project on chemical literacy on the topic of alcohol phase f is expected to assist teachers in overcoming obstacles in making learning media. It can be used as one of the learning media that can help students in learning, especially on alcohol. Testing the content validity and construct validity was carried out by five validators (Padang State University lectures and teachers of senior high school). The data obtained from the validator was then analyzed using Aiken’s V formula. The results of data analysis in this study showed that the average results of Aiken's V on content validity were 0.89, and construct validity was 0.90, which is included in the valid category.